Understanding The Right Of Allah: A Quranic And Sunnah-Based Perspective - Syed Mohamad Zainudin Bichk Koyak; Muhammad Akmaluddin Mohd Hamdan; Ahmad Salahuddin M Azizan (Usuli Faqih Research Centre PLT., 2025)
Indexed Publication (Tier 2)